A Transformative Collegiate Discourse - Evan Ortlieb (SAGE Open, 2011)
The languages, attitudes, experiences, and interests of groups of people are often interconnected through discourses. Within collegiate courses, systems of connected individuals progress through learning opportunities, often led by their professors. During one graduate course at Louisiana State University, two students acted as research investigators studying the unique characteristics of a collegiate discourse. The findings indicate that authors of the study were members of the discourse, topics of discussion were guided by only those students in attendance, and there was reciprocity in teaching and learning between active members of the discourse.